TOURIST ACTIVATION OF DEGRADED AREAS ON THE EXAMPLE OF POST-PIT SULPHUR MINE “MACHÓW” - Michał Rudnicki (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article presents the activation of a specific type of tourist space which is completely degraded natural and scenic areas, until recently, functioning of heavy industry. The analysis was carried out based on the actions of government authorities at central, municipal authorities and specially appointed Tarnobrzeg Sulphur Mine Company “Machów” SA. The main task of this cooperation is to work towards the restoration of natural resources, landscape and the proper management of excavation of the former tourist Sulphur Mine “Machów” in order to stimulate economic activity in this area. This analysis is carried out in two ways. On one hand, it focuses on actions that have already been made, on the other hand reveals plans for tourist development and activities undertaken by the above mentioned entities. At the same time, this test is an attempt to evaluate all completed projects and an indication for a number of other regions of the samples taken at the former tourism recovery.